Mutations Found in embCAB, embR, and ubiA Genes of Ethambutol-Sensitive and -Resistant Mycobacterium tuberculosis Clinical Isolates from China. (31st August 2015) - Xu, Yuhui; Jia, Hongyan; Huang, Hairong; Sun, Zhaogang; Zhang, Zongde
Abstract : To better understand the molecular mechanisms of Ethambutol (EMB) resistance, the mutant hot spot region of five genes ( embB, embA, embC, embR, and ubiA ) was amplified and sequenced in 109 EMB-resistant and 153 EMB-susceptible clinical isolates from China. Twenty-seven EMB-susceptible isolates were found to have nonsynonym mutations, 23 of which were in embB . The mutations occurred most frequently in embB (85.3%, 93) and were seldom in embC (2.8%, 3), embA (3.7%, 4), embR (3.7%, 4), and ubiA (8.3%, 9) in EMB-resistant isolates. For the embB gene, 63 isolates showed mutations at embB 306, 20 at embB 406, nine at embB 497, and five at embB 354 in EMB-resistant isolates. In addition, the particular mutants at embB 406 and embB 497 indicated both high levels of EMB resistance (MICs > 5   μ g/mL) and broad anti-TB drug resistance spectrums. Our data supported the facts that embB 306 could be used as a marker for EMB resistance with a sensitivity of 57.8% and a specificity of 78.8%.